Structure and genetic relationships between Brazilian naturalized and exotic purebred goat domestic goat (Capra hircus) breeds based on microsatellites - Oliveira, Joelliton Domingos de; Igarashi, Maria Luiza Silveira de Paiva [UNESP]; Machado, Théa Mírian Medeiros; Miretti, Marcos Mateo [UNESP]; Ferro, Jesus Aparecido [UNESP]; Contel, Eucleia Primo Betioli (Sociedade Brasileira de Genética, 2007)
The genetic relationships and structure of fourteen goat (Capra hircus) populations were estimated based on genotyping data from 14 goat populations (n = 410 goats) at 13 microsatellite loci. We used analysis of molecular variance (AMOVA), principal component analysis (PCA) and F statistics (F IS, F IT and F ST) to evaluate the genetic diversity (Ho, He and ad) of the goats. Genetic distances between the 14 goat populations were calculated from allelic frequency data for the 13 microsatellite markers. Moderate differentiation was observed for the populations of the undefined breeds (including the Anglo-Nubian-M breed), the naturalized Brazilian breeds (Moxotó, Canindé), the exotic purebred breeds (Alpine, Saanen, Toggenbourg and Anglo-Nubian) and the naturalized Brazilian Graúna group. Our AMOVA showed that a major portion (88.51%) of the total genetic variation resulted from differences between individual goats within populations, while between-populations variation accounted for the remaining 11.49% of genetic variation. We used a Reynolds genetic distance matrix and PCA to produce a phenogram based on the 14 goat populations and found three clusters, or groups, consisting of the goats belonging to the undefined breed, the naturalized breeds and the exotic purebred breeds. The closer proximity of the Canindé breed from the Brazilian state of Paraíba to the Graúna breed from the same state than to the genetically conserved Canindé breed from the Brazilian state of Ceará, as well as the heterozygosity values and significant deviations from Hardy-Weinberg equilibrium suggests that there was a high number of homozygotes in the populations studied, and indicates the importance of the State for the conservation of the local breeds. Cataloguing the genetic profile of Brazilian goat populations provides essential information for conservation and genetic improvements programs.
Keywords: Goat; Microsatellite; genetic distance; PCA; AMOVA; genetic relationships; Genetic diversity; F statistics